CURRENT STATE OF DEVELOPMENT OF THE INSURANCE MARKET IN UKRAINE - SYDORCHUK, IVANNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The given statistical data show that the interest of Ukrainians in insurance and the level of financial literacy of the population is growing, trust in insurance services is increasing. However, the crisis related to the COVID-19 pandemic and the economic crisis in 2020 continued to have a moderate impact on insurers. Insurers’ insurance premiums reported to the National Bank maintained an upward trend, but the increase was halved. The problematic consequences of the pandemic for insurers are: reduction of the share of insurance premiums for aviation insurance and property insurance; reducing the number of contracts related to new car insurance; difficulty in the organization of remote customer service by employees of the insurance company, namely the assessors of insurance losses; elimination of small insurance companies that failed to organize quality online services. The pandemic has led to both positive and negative consequences in the activities of domestic insurers. It gave a new impetus to the development of insurance culture among Ukrainian citizens. People began to understand the importance of such a service, especially life and health insurance. Therefore, it can be argued that most insurance companies in the market were able to adjust and find solutions for stable operation in conditions of economic danger. Thus, according to the current process of formation of the insurance market in Ukraine, we came to the conclusion that its further successful development will depend on: effective control over the activities of insurers by the state; strengthening the capital requirements of insurers, their solvency and assets; adaptation of domestic insurance legislation in accordance with the norms, rules and requirements of European and world markets; introduction of innovative insurance technologies and the latest service quality standards in this area; creation of associations of insurers on the most important insurance issues; creation of a comprehensive system of training and retraining; promotion of insurance services among the population.